O uso do Hand Talk como apoio na comunicação entre surdos e ouvintes de uma Escola Municipal de Taperoá-PB - Sousa, Geruza Pereira de (2025)
he presented e-book constitutes an educational product developed within the scope of the Professional Master’s in Inclusive Education (PROFEI/UEPB), and aims to demonstrate how the technological application Hand Talk can assist in the communication process between students and teachers in school contexts that do not have the support of a Libras interpreter. This material is the result of a master’s research that reflects the commitment to inclusion and communicational accessibility in the school environment. At the beginning, the e-book addresses the importance of using technologies in the educational process, highlighting that we live in a digital and interconnected society. Then, it presents an overview of the historical path of the inclusion of deaf people in education, showing achievements, advances, and challenges still present in this field. Finally, the material is complemented with illustrations and signs of words from everyday school and social life, which seek to facilitate communication between deaf students, hearing classmates, teachers, and other members of the school community, contributing to a more inclusive, accessible, and meaningful pedagogical practice.